On the different ways of being a bi-dialectal immigrant: the case of Argentineans in Spain. - Von-Essen, María Clara (Editorial Universidad de Alcalá, 2020)
This paper aims at analysing the accommodation (convergence) of young immigrants, born in Buenos Aires, Argentina, but living in Malaga, Spain (n = 22). Our main goals are a) to establish why young immigrants adopt diff erent linguistic behaviour in regard to their variety of origin (spoken by their parents, Dl-BAS) and the new variety they have contact with as a result of immigration (D2-MAL), b) to determine what this behaviour reveals about their individual characteristics and the speech communities to which they belong to. Attention has been focused on several linguistic levels: phonology, morphology (syntax) and lexis. Based on our results, the immigrants were classified by two-step cluster analysis in three groups: one is almost completely divergent (conserving Dl-BAS), another shows mixed linguistic behaviour and seems to be bidialectal (Dl+D2), and the third exhibits almost full accommodation towards D2-MAL. This paper aims to be a comprehensive analysis of how speakers readjust their own varieties and display new identities through accommodation (convergence) or divergence.
Keywords: Español - Dialectología; Inmigrantes - Argentina; Varieties of Spanish in contact; Immigration; Accommodation (convergence); Divergence